After Unemployment Benefits are Exhausted - Myers, Charles A.; MacLaurin, W. Rupert (Quarterly Journal of Economics, 1942)
Scope of the study, 231. — The adequacy of unemployment benefits, 233. — Nature of the labor market studied, 235. — Characteristics of the sample, 239. — Experience after benefit exhaustion, 244. — Limitations of the interview method, 250. — Summary and conclusions, 252.